1998
DOI: 10.1007/s002210050474
|View full text |Cite
|
Sign up to set email alerts
|

The role of the pedunculopontine tegmental nucleus in relation to conditioned motor performance in the cat

Abstract: The activity of the pedunculopontine tegmental nucleus (PPTg) neurons was recorded in three unrestrained cats operantly conditioned to perform a lever-release movement. The movement had to be initiated either rapidly after a (click) stimulus in a simple reaction-time paradigm or had to be delayed after the same stimulus in trials identified by a tone cue. Successful trials were rewarded by a food pellet. A total of 107 neurons were recorded with microelectrodes. Brief spike neurons (mean duration: 0.7 ms) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
63
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 72 publications
11
63
0
Order By: Relevance
“…Cholinergic neurons are more prevalent in the caudal PPN, and the presence of gait disorders has been correlated with loss of these cells [14][15][16] . As wide-spike neurons had a significantly lower density than narrow-spike neurons, and were more common in the caudal PPN, these cells are likely to be cholinergic neurons 40 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cholinergic neurons are more prevalent in the caudal PPN, and the presence of gait disorders has been correlated with loss of these cells [14][15][16] . As wide-spike neurons had a significantly lower density than narrow-spike neurons, and were more common in the caudal PPN, these cells are likely to be cholinergic neurons 40 .…”
Section: Discussionmentioning
confidence: 98%
“…Cholinergic neurons are more prevalent in the caudal PPN, and the presence of gait disorders has been correlated with loss of these cells [14][15][16] . As wide-spike neurons had a significantly lower density than narrow-spike neurons, and were more common in the caudal PPN, these cells are likely to be cholinergic neurons 40 .Limb movement and imagined gait had diverse effects on neural activity in the PPN 33 , but resulted in an overall reduction in activity. The PPN has extensive connections with the basal ganglia 5, 11 , receiving strong inhibitory inputs from both the globus pallidus internus and substantia nigra 41 .…”
mentioning
confidence: 98%
“…The reward delivery neurons may receive the actual reward signals from the lateral hypothalamus (Rolls et al, 1980;Fukuda et al, 1986;. This pathway directly excites the PPTN (Semba & Fibiger, 1992), which responds with a brief burst and then accommodates or habituates (Takakusaki et al, 1997;Dormont et al, 1998). This brief burst, in turn, directly excites the midbrain dopamine neurons via cholinergic and glutamatergic projections (Conde, 1992) and thereby causes a phasic burst in dopamine neurons projecting to the striatum (Gerfen, 1992) for actual reward.…”
Section: Possible Primary Reward Signal In the Pptnmentioning
confidence: 99%
“…A number of studies have found impairments in learning following excitotoxic lesions of the PPTN (Fujimoto et al, 1989;Fujimoto et al, 1992;Steckler et al, 1994;Inglis et al, 2000;Alderson et al, 2002). Thus, abundant anatomical, electrophysiological and pharmacological studies of slice and whole animal preparations indicate that the PPTN receives signals from the reward related structures including the cerebral cortices and the striatum (Winn et al, 1997) and provides strong excitatory inputs to the dopamine neurons (Clements & Grant, 1990;Blaha & Winn, 1993;Futami et al, 1995;Oakman et al, 1995;Blaha et al, 1996;Conde et al, 1998;Dormont et al, 1998;MenaSegovia et al, 2004;Pan & Hyland, 2005;Mena-Segovia et al, 2008). Interestingly, the dopamine/ acethylcholine interaction seems to be mutual (Scarnati et al, 1987); dopmine neurons in the substantia nigra pars compacta tproject back to PPTN neurons, affecting their excitability.…”
mentioning
confidence: 99%
“…They have a key role in attention and sensory processes that are needed for proper selection of motor responses to stimuli that are of behavioral significance [111][112][113][114]. Because PPTg neurons also respond to the presentation of stimuli of behavioral significance [115,116], the striatum may process behavior-related signals carried through the PPTg-Pf pathway. The excitatory neurons that form this pathway would ensure a fast route for the conduction of sensory information to the striatum.…”
Section: Understanding the Roles That Pptg May Exert In Cognition Andmentioning
confidence: 99%